Global imbalances: Strategic prospects for the US and the world - Dimitri B. Papadimitriou (Intervention. European Journal of Economics and Economic Policies, 2009)
First paragraph: The prospects for world trade, the motor of growth for many countries for almost a decade, are discouraging especially during a time the global economy is enduring a recession. Since the summer of 2007, trade declined and was exacerbated when trade finance became difficult to obtain for importers, and consumer confidence dropped to unprecedented lows. In December 2008, exports were down in Brazil, China, South Korea and Taiwan by 2, 2.8, 17.4 and 42 percent respectively while in November 2008 exports from the US, Germany, Japan and India were correspondingly lower by 4, 22, 12 and 10 percent respectively – all significant declines (Patel/Trivedi 2009, Norris 2009). Expectations and consensus forecasts for the first quarter of 2009 suggest a decrease in overall trade value around 15 percent in both the advanced and emerging economies and a three percent contraction for the entire year, in real terms. These conditions demonstrate the synchronized slowdown of global demand and the implausibility of any economy to »export its way out of trouble« (Norris 2009). Furthermore, history is full of events illustrating protectionism attempts in many countries intended at improving their trade position with detrimental effects on others. This paper argues that the US and the rest of the world will not be able to achieve balanced growth and full employment unless they are able to agree and implement an entirely new way of running the global economy. In what follows, we outline the nature and magnitude of the emerging crisis, and suggest some of the things that must happen, even if our suggestions for achieving these things might be considered weak.
Keywords: 330